Geomodeling - Mallet, Jean-Laurent (Applied geostatistics series., 2002)
1. Discrete Modeling for Natural Objects. 2. Cellular Partitions. 3. Tessellations. 4. Discrete Smooth Interpolation. 5. Elements of Differential Geometry. 6. Piecewise Linear Triangulated Surfaces. 7. Curvilinear Triangulated Surfaces. 8. Elements of Structural Geology. 9. Stochastic Modeling. 10. Discrete Smooth Partition. Index.